Genetic Relationship between Streptococcus pneumoniae Isolates from Nasopharyngeal and Cerebrospinal Fluid of Two Infants with Pneumococcal Meningitis - de Andrade, Ana Lucia Sampaio Sgambatti (American Society for Microbiology, 2003)
The molecular epidemiology of Streptococcus pneumoniae isolates from carriage and cerebrospinal fluid (CSF) concurrently recovered from the same individual has not yet been reported. By using pulsed-field gel electrophoresis, we demonstrated the genetic linkage among strains from CSF and nasopharynges of two children with pneumococcal meningitis.